Cardiovascular and autoimmune diseases in females: The role of microvasculature and dysfunctional endothelium. Issue 1 (July 2015) - Gianturco, L.; Bodini, B.D.; Atzeni, F.; Colombo, C.; Stella, D.; Sarzi-Puttini, P.; Drago, L.; Galaverna, S.; Turiel, M.
Abstract: Cardiovascular (CV) diseases are becoming increasingly frequent and associated with a high incidence of CV events, disability and death. It is known that there is a relationship between CV burden and systemic autoimmune diseases (SADs) that is mainly due to inflammation and autoimmunity, but the other mechanisms underlying the high CV risk of SAD patients have not yet been fully clarified. The aim of this review article is to discuss some of the specific factors associated with the accelerated atherosclerosis (ATS) characterising SADs (female sex, the microcirculation and the endothelium) in order to highlight the importance of an early diagnosis and the prompt implementation of preventive measures, as well as the possible role of new therapeutic strategies such as vaccine immunomodulation. Finally, as the natural history of ATS begins with endothelial injury (a potentially reversible process that is influenced by various factors) and microvascular damage plays a central role in the etiopathogenesis of SADs, it underlines the crucial need for the development of reliable means of detecting sub-clinical abnormalities in the microcirculation, particularly coronary microcirculation dysfunction. Highlights: There is a relationship between CV burden and SADs. The relationship is mainly due to inflammation and autoimmunity. It is still debated if it is predominant inflammation or autoimmunity. Sex-related studies could give further important support for management of CV damage in SADs. However, nowadays our knowledge is still poor.